Fishermen-Household‘s Accessibilities to Solving Problems of Their Poverty :A Case Study in the East Java Coastal Villages - Muhammad, Sahri; lslamy, lrfan; Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2006)
The objectives of the research are (1) to identify a change for bio-physic livelihoods. to solving their poverty and to disempowering home marine social economy, (2) to analyse factors inï¬‚uencing the strategy of resource usage and ï¬shermen empowerment and (3) to analyse accessibilities of poor home ï¬shermen in solving their needs. The research used a survey method and a poverty rapid appraisal (PRA). Primary data are collected from home ï¬sherman respondents using Participatory Poverty Assessment {PPA) and Sustainable Livelihoods Approaches (SLA). Data was analysed using descriptive and inferential statistics with an analysis model of Ordinary Least Squares (OLS) and Two Stage Least Squares (ZSLS), and Structural Equation Modeling (SEM). The results of the ï¬rst-year research are as follows: (1) exploitation pressures on coastal marine resources are very intensive and exceed maxirnum sustainable yield (MSY) (over exploited). (2) Fishing operations of the ï¬shemien are far away ï¬shing locations, quantity and ï¬sh-size are smaller. Some poor ï¬sliermen solved their problems by using size~renovation of their ships and adjusting catching ï¬sh technology, ï¬shing ground. post-harvest activities.